Electrical injury causing ventricular arrhythmias. Issue 3 (March 1987) - Jensen, P J; Thomsen, P E; Bagger, J P; Nørgaard, A; Baandrup, U
Abstract : Dangerous or long lasting ventricular arrhythmias developed in three patients who had sustained an electrical injury in which current passed through the thorax. In all three cases there was a delay of 8-12 hours between the injury and the onset of symptoms. The ventricular arrhythmias were severe and long lasting. In two of the three patients, ventricular tachycardia or ventricular fibrillation or both occurred and in one patient ventricular parasystole developed. No enzymatic evidence of myocardial necrosis was found but the results of an endomyocardial biopsy carried out in two of the three patients showed focal myocardial fibrosis and increased numbers of Na, K-pumps. The two patients with ventricular tachycardia became symptom free after appropriate antiarrhythmic treatment and in the third patient ventricular parasystole disappeared spontaneously within two years. Patients sustaining electrical injury in which current passes through the thorax should be monitored electrocardiographically for at least 24 hours, and patients with unexpected arrhythmias should be questioned about previous electrical injury.